FRI0302 Tocilizumab, DMARDS and Glucocorticoids in Rheumatoid Arthritis – Interim Analysis of the German Non-Interventional Study Ichiban. (10th June 2014) - Specker, C.; Kaufmann, J.; Vollmer, M.A.; Kellner, H.; Höhle, M.; Kühne, C.; Volberg, C.; Henes, J.C.; Zinke, S.; Moosig, F.; Bohl-Bühler, M.; Sieburg, M.; et al.
Abstract : Background: The ICHIBAN study collects routine clinical data to evaluate the effectiveness and safety of tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) in real world practice over a period of 2 years. Methods: The start of this prospective, non-interventional study was in February 2010. The target recruitment is 4000 patients. Therapeutic data, relevant progression parameters as well as activity scores and adverse events are recorded. Results: As of 1st December 2013, baseline data for 2373 patients with a mean age was 56.4 years were available. 75.9% of these patients were female and the median duration of RA was 7.4 years. The total TCZ exposure was 4084.8 patient years. In 589 patients the duration of observation has reached the intended period of 2 years, or treatment was interrupted or changed before and analysed according to LOCF method. 73.9% were pre-treated with TNF-alpha inhibitors, 24.6% exclusively with synthetic DMARDs. The mean baseline DAS28 of the 589 patients was 5.6. At the end of observation 36.2% achieved DAS28-ESR remission (<2.6) and 27.5% or 53.8% moderate or good EULAR response, respectively. During observation the proportion of TCZ monotherapy patients increased from 42.8% to 63.8% and MTX combinations decreased by 14.6%. In 23.9% of patients being initially treated with DMARD combination, DMARDs could be discontinued. TCZ monotherapy and combination therapies showed comparable efficacy: 19.3% and 22.0% achieved CDAI remission (≤2.8), respectively. During the observation period the mean daily glucocorticoid (GC) dose decreased continuously from 9.4 (baseline) to 5.3 mg/d (week 104). In 19.2% of patients receiving GCs at baseline they could be discontinued, in 52.7% GC could be reduced and a dose increase was necessary in only 10.0% of the patients. The proportion of patients not needing concomitant GC increased by 11.4% to 29.0% during observation and the proportion of daily GC dose ≤5 mg raised from 59.7% to 76.5% (see figure). Conclusions: This interim analysis of the non-interventional ICHIBAN study includes the first 589 completing patients with moderate to severe RA being observed for the intended period of 2 years of TCZ treatment. The results show clear improvements of activity parameters, reduction of concomitant DMARD and glucocorticoid use. As in controlled studies, TCZ monotherapy was equal effective compared to DMARD, even under real-life conditions. This enduring efficacy was demonstrated for the first time over a long period of 2 years in clinical practice data. Disclosure of Interest: C. Specker Grant/research support: Has received honoraria from Chugai for advising in study design and conduction and fees for talks, in summary less than €10.000/year, J. Kaufmann: None declared, M. Vollmer: None declared, H. Kellner: None declared, M. Höhle: None declared, C. Kühne: None declared, C. Volberg: None declared, J. Henes Grant/research support: Lecture activities for Roche, MSD, ABBVIE and Pfizer, S. Zinke Grant/research support: Abbvie, MSD, Janssen, F. Moosig Grant/research support: Has received honoraria from Chugai/Roche for lectures and consulting, M. Bohl-Bühler: None declared, M. Sieburg Grant/research support: Participation in non-interventional studies from Roche, Pfizer, MSD, BMS, UCB, Abbvie, Medac, M. Aringer Consultant for: Advisory boards Chugai and Roche, M. Hofmann Employee of: Chugai Pharma, P. Hellmann Employee of: Chugai Pharma, G. Fliedner Grant/research support: Has received honoraria from Chugai for advising in study design and conduction and fees for talks, in summary less than €10.000/year DOI: 10.1136/annrheumdis-2014-eular.2331